Sistem Informasi Reservasi Salon dan Perawatan Kecantikan Berbasis Website di Adel Beauty Studio Sukaraya Kota Baturaja - Atika Yohana Zulpa; Muhamad Ihsan; Apriansyah Apriansyah (Journal of Innovative and Creativity, 2025)
The study purpose was to design and evaluate a web-based reservation information system for salon and beauty careservices at Adel Beauty Studio Sukaraya, Baturaja. The development of this system was motivated by the growing needfor digitalization in the beauty service industry, aiming to improve efficiency, reduce booking errors, and enhancecustomer satisfaction through technology-driven innovation.Materials and methods. The system was developed using the PHP programming language and MySQL database,applying the prototyping development model. The website allows customers to register, log in, view available treatmentpackages, select schedules, and confirm reservations online. Administrators can manage user data, booking data,treatment packages, and generate reports efficiently. The functionality of the system was tested using black-box testingto ensure that each feature worked as expected.Results. All functional tests produced results according to the planned design. The online booking system simplifiedthe reservation process, reduced customer waiting times, and minimized manual data errors. The admin modulesuccessfully managed user and transaction data, supporting smoother and more organized operations.Conclusions. The web-based reservation information system proved to be effective, user-friendly, and efficient inmanaging salon services. This system provides a practical solution to improve service quality and operationalperformance while offering potential for future integration with digital payment systems and Internet of Things (IoT)technology.